New Perspectives on Informational Asymmetry and Agency Relationships - Haugen, Robert A.; Senbet, Lemma W. (Journal of Financial and Quantitative Analysis, 1979)
The two related problems of agency and informational asymmetry have received increasing attention in finance. In particular, prominent authors in this area (e.g., Jensen and Meckling [7], Ross [15, 16], Leland and Pyle [10], etc.) have demonstrably argued that the financial structure of the firm can be determined in the process of eliminating, or at least reducing, the costs associated with these problems.